Defining Clinical Subgroups in Relapsing Polychondritis: A Prospective Observational Cohort Study. Issue 8 (8th July 2020) - Ferrada, Marcela; Rimland, Casey A.; Quinn, Kaitlin; Sikora, Keith; Kim, Jeff; Allen, Clint; Sirajuddin, Arlene; Goodspeed, Wendy; Chen, Marcus; Grayson, Peter C.
Abstract : Objective: Relapsing polychondritis (RP) is a systemic disease. Failure to recognize RP can lead to diagnostic delay and further complications, including death. This study was undertaken to identify clinical patterns in a prospective cohort of patients with RP. Methods: Patient subgroups were identified using latent class analysis based on 8 clinical variables: saddle‐nose deformity, subglottic stenosis, tracheomalacia, bronchomalacia, ear chondritis, tenosynovitis/synovitis, inflammatory eye disease, and audiovestibular disease. Model selection was based on Akaike's information criterion. Results: Seventy‐three patients were included in this study. Patients were classified into 1 of 3 subgroups: type 1 RP (14%), type 2 RP (29%), and type 3 RP (58%). Type 1 RP was characterized by ear chondritis (100%), tracheomalacia (100%), saddle‐nose deformity (90%), and subglottic stenosis (80%). These patients had the shortest median time to diagnosis (1 year), highest disease activity, and greatest frequency of admission to the intensive care unit and tracheostomy. Type 2 RP was characterized by tracheomalacia (100%) and bronchomalacia (52%), but no saddle‐nose deformity or subglottic stenosis. These patients had the longest median time to diagnosis (10 years) and highest percentage of work disability. Type 3 RP was characterized by tenosynovitis/synovitis (60%) and ear chondritis (55%). There were no significant differences in sex, race, or treatment strategies between the 3 subgroups. Conclusion: Our findings indicate that there are 3 subgroups of patients with RP, with differences in time to diagnosis, clinical and radiologic characteristics, and disease‐related complications. Recognizing a broader spectrum of clinical patterns in RP, beyond cartilaginous involvement of the ear and upper airway, may facilitate more timely diagnosis.